DOA SEBAGAI SARANA KOMUNIKASI SAKRAL ANTARA MANUSIA DAN TUHAN - Bagus Pande Darma Putra Mahardhita (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
Prayer is a vital aspect of the spiritual life of Hindus, serving as a sacred means of communication between humans and God. In Hindu tradition, prayer is not merely a formal ritual but a profound connection encompassing spiritual, moral, and social dimensions. Through prayer, individuals express gratitude, seek guidance, and attain inner harmony and cosmic balance. This article analyzes prayer from the perspective of Hindu communication, highlighting its symbolic, philosophical, and practical aspects. In this vertical communication, elements such as mantras, mudras, and offerings play a significant role in enriching the spiritual experience. Additionally, prayer serves as a medium for introspection and emotional transformation, enabling individuals to achieve peace and enlightenment. This study reveals that prayer is not only spiritually relevant but also contributes to character formation and the preservation of dharma values in modern life.